2023
DOI: 10.7554/elife.89134
|View full text |Cite
|
Sign up to set email alerts
|

Comment on 'Parasite defensive limb movements enhance acoustic signal attraction in male little torrent frogs'

Nigel K Anderson,
Doris Preininger,
Matthew J Fuxjager

Abstract: Zhao et al. recently reported results which, they claim, suggest that sexual selection produces the multimodal displays seen in little torrent frogs (Amolops torrentis) by co-opting limb movements that originally evolved to support parasite defense (Zhao et al., 2022). Here, we explain why we believe this conclusion to be premature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Recently we showed that movements associated with anti-parasite behavior can act on female perception and may thereby affect the evolution of a multimodal display in little torrent frogs ( Amolops torrentis ) ( Zhao et al, 2022 ). Anderson et al provide some alternative interpretations for our findings, some of which we found useful for discussion and future experiments ( Anderson et al, 2023 ). Their most important argument concerns our finding that females showed a strong preference for limb movements that were not strongly associated with the presence of eavesdropping parasites.…”
Section: Introductionmentioning
confidence: 53%
“…Recently we showed that movements associated with anti-parasite behavior can act on female perception and may thereby affect the evolution of a multimodal display in little torrent frogs ( Amolops torrentis ) ( Zhao et al, 2022 ). Anderson et al provide some alternative interpretations for our findings, some of which we found useful for discussion and future experiments ( Anderson et al, 2023 ). Their most important argument concerns our finding that females showed a strong preference for limb movements that were not strongly associated with the presence of eavesdropping parasites.…”
Section: Introductionmentioning
confidence: 53%